2021
DOI: 10.1111/jocs.15571
|View full text |Cite
|
Sign up to set email alerts
|

Right anterior mini thoracotomy approach for isolated aortic valve replacement: Early outcomes at a Canadian center

Abstract: Objective: The goal of this manuscript was to report the clinical outcomes of the initial series of 100 consecutive Right Anterior Mini Thoracotomy (RAMT) aortic valve replacement (AVR) implantations at a Canadian Center.Methods: This retrospective study reported the clinical outcomes of the first 100 patients who underwent the RAMT approach for isolated surgical AVR in Calgary, Canada, between 2016 and 2020. Primary outcomes were death within 30 days of surgery and disabling stroke. Secondary outcomes include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 53 publications
(107 reference statements)
0
6
0
Order By: Relevance
“…Minimally invasive cardiac surgery has been widely adopted worldwide and is showing a growing trend. Complex cardiac surgical procedures using the RAMT approach are increasingly performed in many cardiac surgery centers worldwide [7][8][9][10][11][12]. The aim of minimally invasive surgery is to avoid a complete sternotomy and its associated complications by reducing the morbidity and mortality [7,28,29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Minimally invasive cardiac surgery has been widely adopted worldwide and is showing a growing trend. Complex cardiac surgical procedures using the RAMT approach are increasingly performed in many cardiac surgery centers worldwide [7][8][9][10][11][12]. The aim of minimally invasive surgery is to avoid a complete sternotomy and its associated complications by reducing the morbidity and mortality [7,28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Since the late 1990s, minimally invasive surgery via right anterolateral mini-thoracotomy (RAMT) access has been increasing and gaining popularity in cardiac surgery in order to optimize surgical procedures and results. Actually, minimally invasive surgery via RAMT has become established in many centers worldwide in the field of valve surgery [1][2][3][4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Minimally invasive cardiac surgery has been widely adopted worldwide and is showing a growing trend. Complex cardiac surgical procedures using the RAMT approach are increasingly performed in many cardiac surgery centers worldwide [7][8][9][10][11][12]. The aim of minimally invasive surgery is to avoid a complete sternotomy and their associated complications by reducing the morbidity and mortality [7,28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Since the late 1990´s minimally invasive surgery via right-anterolateral mini-thoracotomy (RAMT) access has been increasing and gaining popularity in cardiac surgery in order to optimize surgical procedures and results. Actually, minimally invasive surgery via RAMT has become established in many centers worldwide in the field of valve surgery [1][2][3][4][5][6][7][8][9][10][11][12]. The standard surgical approach for the treatment of pathologies of the ascending aorta (AA) and the aortic root is the Disclaimer/Publisher's Note: The statements, opinions, and data contained in all publications are solely those of the individual author(s) and contributor(s) and not of MDPI and/or the editor(s).…”
Section: Introductionmentioning
confidence: 99%
“…We have read with great interest about Fatehi et al's experience of right anterior mini thoracotomy approach for isolated aortic valve replacement (AVR). 1 We also congratulate the authors on the quality of their work, which provides a valuable experience about minimally invasive AVR. They demonstrated in a retrospective study that minimally invasive AVR provides favorable short-term clinical outcomes, reduces postoperative bleeding and the requirement for anesthesia, and concluded that minimally invasive AVR could be a reliable treatment.…”
mentioning
confidence: 95%